2014
DOI: 10.1371/journal.pone.0087032
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Validation of Oncologic miRNA Biomarkers for Luminal A-like Breast Cancer

Abstract: IntroductionBreast cancer is a common disease with distinct tumor subtypes phenotypically characterized by ER and HER2/neu receptor status. MiRNAs play regulatory roles in tumor initiation and progression, and altered miRNA expression has been demonstrated in a variety of cancer states presenting the potential for exploitation as cancer biomarkers. Blood provides an excellent medium for biomarker discovery. This study investigated systemic miRNAs differentially expressed in Luminal A-like (ER+PR+HER2/neu-) bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
0
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(75 citation statements)
references
References 42 publications
(26 reference statements)
3
70
0
2
Order By: Relevance
“…Therefore, miR-93, rather than the whole cluster and its host gene, may play a critical role in the acquisition of drug resistance in breast cancer. To date, very few studies have focused on the role of miR-93 in breast cancer (30)(31)(32)(33)(34)(35)(36). Furthermore, these studies only reported its association with altered expression patterns and proliferation, and none have focused on its relationship with drug resistance and association with PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, miR-93, rather than the whole cluster and its host gene, may play a critical role in the acquisition of drug resistance in breast cancer. To date, very few studies have focused on the role of miR-93 in breast cancer (30)(31)(32)(33)(34)(35)(36). Furthermore, these studies only reported its association with altered expression patterns and proliferation, and none have focused on its relationship with drug resistance and association with PTEN.…”
Section: Discussionmentioning
confidence: 99%
“…78 This method was successfully applied for the discovery of altered miRNAs between luminal A breast cancer patients and healthy controls. 79 …”
Section: Data Processing and Miningmentioning
confidence: 99%
“…These particular miRNAs were selected on the basis of previous reports in the literature, the miRNA database, and communications from breast cancer conferences. They represent a broad range of epigenetic pathways involved in migration, invasion, receptor status, epithelialto-mesenchymal transition, cancer dormancy, switch to the fast growing phenotype, drug resistance, etc (Blenkiron et al, 2007;Lowery et al, 2008;Fang et al, 2012;Liu et al, 2012;Manavalan et al, 2013;Lehmann, 2014;Li et al, 2014;McDermott et al, 2014;www.mirbase.org). We also used unpublished data of TaqMan Low Density Arrays from our previous research.…”
Section: Mirna Expressionmentioning
confidence: 99%
“…Breast cancerrelated genes have been extensively investigated (Ellis and Perou, 2013), but much less is known about epigenetic alterations such as microRNAs (miRNAs), DNA methylation, or histone modifications (Lehmann, 2014;Li et al, 2014;McDermott et al, 2014). MiRNAs are single-stranded, small noncoding RNAs, *18-25 nucleotides in length that potentially may modify up to one-third of the human genome (Fang et al, 2012;Li et al, 2014;McDermott et al, 2014). They were first identified over a decade ago and in February 2014, a total of 2578 human miRNAs were registered in mirbase.org (www.mirbase.org).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation